2010
DOI: 10.1097/mat.0b013e3181dbefd0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Survival in Patients With Cardiogenic Shock and Multiorgan Failure Treated With Biventricular Assist Device

Abstract: Mechanical circulatory support (MCS) is valuable in saving the lives of patients with severe cardiogenic shock. However, their survival is limited if multiorgan failure (MOF) proves to be irreversible. Although ventricular assist devices (VADs) have been shown to reverse end-organ failure in some patients, the pathophysiological mechanisms of end-organ failure and its regression are not fully understood, and clinical markers and thresholds for the "point of no return" are lacking. We investigated predictors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
3
10
0
1
Order By: Relevance
“…Despite the disease's different etiologies, factors such as older age are known risk factors of dying on BVAD support [17]. This fact could be affirmed by our study as group 1 patients were younger than group 2 patients.…”
Section: Discussionsupporting
confidence: 72%
“…Despite the disease's different etiologies, factors such as older age are known risk factors of dying on BVAD support [17]. This fact could be affirmed by our study as group 1 patients were younger than group 2 patients.…”
Section: Discussionsupporting
confidence: 72%
“…Earlier implementation of advanced circulatory support (e.g., by VAD) may improve the outcome in patients with post-cardiotomy cardiogenic shock. [7][8][9] In some cases, a combination of the two devices, the TandemHeart for right and the Impella for short-term left ventricular support, may be helpful. 10 The recent introduction of the Levitronix pump (Levitronix, Waltham, MA), employing magnetic levitation for short-term support, 11 did not solve the problems of patient selection, severe multi-organ failure or need for thoracotomy in some cases, but advanced technology with a low level of hemolysis allows the pump to run for several weeks and the support to be weaned at low speed.…”
Section: Advances In Short-term Support For Acute Heart Failurementioning
confidence: 98%
“…In recent years many scores have been developed to predict outcome after VAD implantation. 7,9,20,21 Klotz et al found that easily obtained and quickly accessible clinical parameters can inform potential patients, relatives and physicians pre-operatively about the risk of death in the intensive care unit (ICU) after VAD implantation. 9 Similar to previous studies, the Seattle Heart Failure Model allows prediction of the major features of a patient's course post-operatively, including length of hospital stay and 1-year survival.…”
Section: Advances In Long-term Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…1 AST indicates aspartate aminotransferase; BP, blood pressure; CI, cardiac index; CVP, central venous pressure; IABP, intra-aortic balloon pump; PAP, pulmonary artery pressure; PAPI, pulmonary artery pulsatility index; PCWP, pulmonary capillary wedge pressure; RA, right atrial; RVAD, right ventricular assist device; and SVR, systemic vascular resistance.…”
Section: Discussionmentioning
confidence: 99%